2015
DOI: 10.1371/journal.pone.0132031
|View full text |Cite|
|
Sign up to set email alerts
|

Rebamipide Promotes the Regeneration of Aspirin-Induced Small-Intestine Mucosal Injury through Accumulation of β-Catenin

Abstract: BackgroundThe effect of rebamipide on repairing intestinal mucosal damage induced by nonsteroidal anti-inflammatory drugs and its mechanism remain unclear. In this study, we sought to explore the mechanism whereby rebamipide could promote the regeneration of aspirin-induced intestinal mucosal damage.MethodsBALB/c mice were administered aspirin (200 mg/kg/d) for 5 days to induce acute small intestinal injury (SII). Subsequently, SII mice were treated with rebamipide (320 mg/kg/d) for 5 days. The structure of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
4
19
0
6
Order By: Relevance
“…To investigate the effects of rebamipide on the intestine, we used abdominal irradiation for mice to reduce the radiationinduced bone marrow injury. There are many reports of therapeutic effects of rebamipide on small intestinal injury [22][23][24] ; however, reports related to radiation-induced colonic injury are limited. Colitis is a clinical side effect of radiotherapy, which involves the gut microflora and induces colonic endotoxemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of rebamipide on the intestine, we used abdominal irradiation for mice to reduce the radiationinduced bone marrow injury. There are many reports of therapeutic effects of rebamipide on small intestinal injury [22][23][24] ; however, reports related to radiation-induced colonic injury are limited. Colitis is a clinical side effect of radiotherapy, which involves the gut microflora and induces colonic endotoxemia.…”
Section: Resultsmentioning
confidence: 99%
“…21 Application of rebamipide alleviates the inflammation in the small intestine through its anti-inflammatory effects and activation of the Wnt/β-catenin pathway. 22,23 In this study, because goblet cells play important roles in intestinal barrier damage, we investigated whether rebamipide could attenuate the radiation-induced colitis by inducing differentiation of goblet cells in mice model and human colonic epithelial cell line.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Besides the well-established inhibitory effect of cyclooxygenase (COX), ASA specifically has been recognized to compromise the phospholipid layer in mucus, 11 increasing access to luminal aggressors like lipopolysaccharide and bile, as well as disrupting intestinal permeability and causing inflammation. 12 Given that deleterious compositional changes to the microbiota, in addition to direct effects on mucus and epithelial tissue, may increase the risk of NSAID enteropathy, we hypothesized that an intervention targeting microbiome-host interactions may offer an attractive preventative strategy. Our strain selection was based on the anti-inflammatory properties of certain bifidobacteria 13,14 and experimental preclinical evidence for a role of bifidobacteria in NSAID-associated ulceration, [15][16][17] as well as unpublished preclinical screening data suggesting a particular potential of efficacy for the specific strain belonging to this genus.…”
mentioning
confidence: 99%
“…Furthermore, Watanabe et al [17] conducted a multicenter, randomized, double-blind, placebo-controlled trial to assess the efficacy of rebamipide in patients taking enteric-coated LDA for more than 3 months, and reported that rebamipide, but not placebo, significantly decreased the number of mucosal breaks after 8 weeks of treatment. Lai et al [23] explored the mechanism by which rebamipide promoted the regeneration of aspirin-induced intestinal mucosal damage and reported that the drug could strengthen tight junctions between intestinal epithelial cells and increase COX-2, β-catenin, and PGE2 expression in small intestinal tissues. Watanabe et al [19] also reported the efficacy of misoprostol in the treatment of LDA-induced small bowel mucosal injuries such as red spots and mucosal breaks in patients taking enteric-coated aspirin in a pilot study.…”
Section: Discussionmentioning
confidence: 99%